2004
DOI: 10.1128/jvi.78.19.10814-10819.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Riboswitch Regulates RNA Dimerization and Packaging in Human Immunodeficiency Virus Type 1 Virions

Abstract: The genome of retroviruses, including human immunodeficiency virus type 1 (HIV-1), consists of two identical RNA strands that are packaged as noncovalently linked dimers. The core packaging and dimerization signals are located in the downstream part of the untranslated leader of HIV-1 RNA-the ⌿ and the dimerization initiation site (DIS) hairpins. The HIV-1 leader can adopt two alternative conformations that differ in the presentation of the DIS hairpin and consequently in their ability to dimerize in vitro. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 41 publications
2
99
0
Order By: Relevance
“…15,68,69 These types of conformational switches are important for HIV-1 and MLV, for example, in the encapsidation process. [70][71][72] Furthermore, one major finding suggested that a fraction of the gag mRNA (vRNA) is retained in distinct cytoplasmic compartments in both the absence and presence of Rev. 17 Our results confirm this finding and also reveal how cellular proteins, like hnRNP A2/B1, influence the dynamic formation of these HIV-1 RNA pools by influencing tightly regulated nuclear and cytoplasmic trafficking events.…”
Section: Discussionsupporting
confidence: 77%
“…15,68,69 These types of conformational switches are important for HIV-1 and MLV, for example, in the encapsidation process. [70][71][72] Furthermore, one major finding suggested that a fraction of the gag mRNA (vRNA) is retained in distinct cytoplasmic compartments in both the absence and presence of Rev. 17 Our results confirm this finding and also reveal how cellular proteins, like hnRNP A2/B1, influence the dynamic formation of these HIV-1 RNA pools by influencing tightly regulated nuclear and cytoplasmic trafficking events.…”
Section: Discussionsupporting
confidence: 77%
“…polyA and SD hairpin; Das et al 1997Das et al , 1999aAbbink & Berkhout 2007), which eventually led to the description of an alternative HIV-1 RNA leader structure in which the polyA hairpin is opened to allow base-pairing with the DIS domain (Huthoff & Berkhout 2001;Abbink & Berkhout 2003;Ooms et al 2004). The equilibrium between the two leader conformations may function as a riboswitch that is important in controlling RNA dimerization and packaging.…”
Section: Virus Evolution To Study Structured Rna Signalsmentioning
confidence: 99%
“…Such RNA conformational switches have been elucidated upon dimerization of HIV-1 and MLV RNAs. 11,12,19,[93][94][95][96][97][98][99] However, direct insights into RNA structure-function relationship are needed to validate this hypothesis. Another possibility is that the interaction between the gRNA and Gag, or between the gRNA and a-yet-to-be-identified cellular factor, could modulate the dual targeting of the genome.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%